2013
DOI: 10.1177/0961203313512880
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the hip in Korean patients with systemic lupus erythematosus: risk factors and clinical outcome

Abstract: Advanced ARCO stage at the onset of ON is an independent risk factor for THR in SLE patients with ON. In ARCO stage I-III ON, patients with NPSLE and those receiving > 0.9 g prednisolone during the first six months after the ON diagnosis are likely to require THR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 21 publications
3
31
0
1
Order By: Relevance
“…Some studies of patients with non‐multifocal ON with SLE have reported that ON tends to occur in young patients, usually in the first 5 years after SLE onset . In the cases identified in our retrospective review and our literature review, the onset age of multifocal ON and the interval between the onset of rheumatic disease and multifocal ON were similar to those of non‐multifocal ON.…”
Section: Discussionsupporting
confidence: 64%
“…Some studies of patients with non‐multifocal ON with SLE have reported that ON tends to occur in young patients, usually in the first 5 years after SLE onset . In the cases identified in our retrospective review and our literature review, the onset age of multifocal ON and the interval between the onset of rheumatic disease and multifocal ON were similar to those of non‐multifocal ON.…”
Section: Discussionsupporting
confidence: 64%
“…Immunological conditions such as systemic lupus erythematosus, 11 12 Sjogren’s syndrome, 8 11 dermatomyositis, 8 mixed connective tissue disease, 8 rheumatoid arthritis, 8 adult-onset Still disease 11 or scleroderma 11 have previously been associated with increased risk of ON. These associations may be mediated by use of corticosteroids 8 or other immunosuppressive drugs, 33 or may be related to the specific disease activity itself. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Risk factors related to laboratory results. Overall, studies that investigated the association between aCL and ON did not find a significant association (Figure 4) 3,17,20 26,53,59 , and mycophenolate mofetil 22,26,30,38 were not associated with a higher risk of ON.…”
Section: Rheumatologymentioning
confidence: 95%
“…In fact, some authors found that immunosuppressive therapy is a risk factor for ON 17,22,30,32,42,57 . Conversely, these agents could be surrogates for disease activity, which could be a risk for ON.…”
Section: Rheumatologymentioning
confidence: 99%